Intermodal Matching on the Example of Sound and Color Connection in Norm and Pathology - Dyachenko A. (Клиническая и специальная психология, 2017)
The article describes the initial period of research of synesthesia and further work, experimental and theoretical, related to the study of various intermodal correspondences. Information about the presence of a statistically significant phenomenon of various intermodal correspondences in healthy people (which includes for example the connection of sound and color) is provided. Present experiment reveals that the phenomenon of sound-color correspondences undergoes destructive changes in patients with schizophrenia compared with that in healthy individuals, but does not detect new distinct patterns.